Healing Springs of Russia - Malkhazova, Svetlana. author. aut Link
XVII, 161 p. 113 illus., 106 illus. in color.
Keywords: This book provides the first diverse and multifaceted textual and cartographic overview of natural curative resources of mineral waters and peloids in Russia. In a readily understandable way the book informs about the genesis, history of exploration and geographical features of water springs, their properties and use as healing springs, as well as specifics and prospect of their contemporary use. The monograph features numerous color illustrations and photos and is oriented toward a general audience but also appeals to geographers, environmental and public health workers and other specialists interested in environmental and public health issues.